The Role of Artificial Intelligence in Enhancing Digital and Data Literacy among Secondary School Students: A Systematic Literature Review - Duwi Purnama Sidik; Fitri Irawijayanti; Fatqurhohman Fatqurhohman (Ihsan Cahaya Pustaka, 2025)
The advancement of artificial intelligence (AI) has brought significant changes to the learning paradigm in secondary schools, particularly in the development of digital literacy, data literacy, and 21st-century skills. This study aims to systematically review the role of AI in enhancing these competencies through a Systematic Literature Review (SLR), analyzing scholarly articles published between 2020 and 2025 from various international databases. The findings indicate that AI implementation can foster adaptive and personalized learning, while also improving students’ critical thinking, collaboration, and creativity skills. However, several challenges remain, including limited technological infrastructure, teacher readiness to utilize AI, and ethical and data privacy concerns that need careful consideration. Overall, AI has great potential as a catalyst for inclusive, effective, and sustainable educational transformation, provided it is supported by appropriate policies and enhanced educator competencies to optimize the use of technology.